UJI VALIDITAS SIRIRAJ STROKE SCORE, ALGORITMA STROKE GADJAH MADA, SKOR STROKE NUARTHA TERHADAP COMPUTERIZED TOMOGRAPHY SCAN KEPALA DALAM MENENTUKAN JENIS STROKE PADA FASE AKUT - Lestari, Trisna; Artini, Yuli; Noor, Farida; Permanaputra, Ariebuana; Ramadani, Claranur (Fakultas Kedokteran Universitas Islam Al-Azhar, 2020)
Stroke is a syndrome that is characterized by sudden functional focal and global brain disorder that develops very quickly lasting more than 24 hours (unless there is surgical intervention or bringing death) caused by vascular disorder in the brain (Gofir, 2009). Stroke is the number one cause of serious disability settled worldwide. Stroke is also a leading cause of death worldwide. This research had 87 sample, consisting of 50 men and 37 women. The study was done using patient suspect stroke that enter the emergency room. The analysis result was nuartha’s stroke score has the highest sensitivity and specificity compared to Siriraj Stroke Score and Gadjah Mada Stroke Score. The sensitivity of the Nuartha Stroke Score in diagnosing non hemorrhagic stroke was 94,87 and with a specificity of 94.12%. Whereas for diagnosing hemorrhagic stroke, nuartha stroke score has a sensitivity of 94,12% and specificity of 94.87%. With an accuracy of 94.64%